EFFECT OF DENTAL IMPLANT DIMENSIONS ON FATIGUE BEHAVIOUR: A NUMERICAL APPROACH - Topkaya, Hüsna; Kaman, Mete Onur (My University, 2018)
In this study, the effect of the implant shape on fatigue behavior was investigated with thefinite element method. The implant material used was Ti6Al4V. The examination focus on the effect onthe implant life with respect to changes in the crest and root dimension, thread depth, thread pitch,implant length, implant diameter, chamfer length, chamfer radius, and groove length to implant lengthratio. Models were subjected to fatigue analysis according to ISO 14801 standard with ANSYS finiteelement software. The mean stress correction theory is chosen in fatigue life solutions. As a result, theparameters seen to have the most effect on dental implant fatigue behavior were the implant length anddiameter. The parameters with the most effect on the implant screw fatigue were pitch and the height ofthe tooth.
Keywords: Mühendislik; Makine; Diş Hekimliği; Malzeme Bilimleri; Özellik ve Test; Malzeme Bilimleri; Biyomalzemeler